Efektivitas Low-Carb Diet vs Low-Fat Diet terhadap Body Composition pada Orang dengan Obesitas: Literature Review: Efektivitas Low-Carb Diet vs Low-Fat Diet terhadap Body Composition pada Orang dengan Obesitas: Literature Review - Indriyani, Tutut Rizki; Rahmawati, Atika; Khoirunnisa, Luthfiani; Wahyurin, Izka Sofiyya (Amerta Nutrition, 2024)
Background: Obesity is still become a serious problem today. Obesity is caused by excessive adipose tissue. One of many factors that contribute to a person's obesity is food intake. Excess carbohydrate and fat intake will be stored in the form of triglycerides in adipose tissue. In the meantime, Low-Carb Diet (LCD) and Low-Fat Diet (LFD) are one of the most popular treatments on obesity. However there are many pros and cons related to each diet based on several studies. Objectives: The indicated study aims to determine the effectiveness of LCD and LFD on body composition in people with obesity. Methods: The study was conducted through journal and literature review, based on five journal publications, filtered by related keywords. In accordance to inclusion and exclusion criteria within the last ten years in Pubmed/Medline database, Science Direct, and Wiley Online Library with the keywords "Low-Carb Diet", "Low-Fat Diet", "Body Mass Index", "Lipid Levels", "Adipose Tissue", "Obese", and "Body Water". Discussion: Total body mass and fat mass decreased significantly after being given LCD intervention compared to LFD. The group that was given two dietary interventions also losing weight, but there was no changes in body water. In addition, negative effects were found from the LCD and LFD interventions such as constipation, fatigue, polyuria, nausea, vomiting, changes in appetite, and headaches. Kidney failure, ketosis, and premature coronary artery also occurred in the group that was given with LCD intervention. Conclusions: LCD and LFD interventions can affect body composition of people with obesity.